Generation of a human induced pluripotent stem cell line from a familial Alzheimer's disease PSEN1 T119I patient - Isaja, Luciana (2021)
Human induced pluripotent stem cells (hiPSC) line FLENIi001-A was reprogrammed from dermal fibroblasts using the lentiviral-hSTEMCCA-loxP vector. Fibroblasts were obtained from a skin biopsy of a 72-year-old Caucasian male familial Alzheimer's disease patient carrying the T119I mutation in the PSEN1 gene. PSEN1 genotype was maintained and stemness and pluripotency confirmed in the FLENIi001-A hiPSC line.